The Relationship between Reading and Writing Skills and Language Dimensions: A Study in Primary School Children with Cochlear Implants - Figueroa, Mario; Bayés, Gemma; Silvestre, Núria (Revista de Investigación en Logopedia, 2025)
Recent research has explored the relationship between linguistic skills and reading competence in children with cochlear implants (CI). However, a notable gap exists within these studies, as many predominantly focus on phonological aspects, neglecting a comprehensive, multidimensional linguistic analysis. Also, the relationship of the different language dimensions with written language skills remains significantly under-investigated in children with CI. To bridge this knowledge gap, we conducted a study involving 30 primary school children with CI. Participants underwent evaluations of their linguistic and literacy skills using the BLOC and TALEC test batteries. Our findings revealed significant associations between reading skills and various language dimensions. Furthermore, writing skills exhibited significant associations with all language dimensions, with the exception of pragmatics. Regression analyses demonstrated that semantic and syntactic skills are key predictors, accounting for substantial variability in both reading and writing abilities. Finally, we discuss these results and propose implications for educational and clinical interventions.